Preparation method of sulfide solid electrolyte membrane and product

By introducing polythiol materials and initiators in the preparation process of the sulfide electrolyte membrane to form a crosslinking network structure, the problem of insufficient mechanical strength of the sulfide solid electrolyte membrane is solved, the mechanical strength and chemical stability of the membrane are improved, and the performance of all-solid state batteries is improved.

CN120413769APending Publication Date: 2025-08-01ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510557458.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing sulfide solid electrolyte membranes have insufficient mechanical strength and are difficult to meet the requirements of high-performance all-solid state batteries.

Method used

After mixing the sulfide electrolyte, polysulfide material and solvent evenly, adding an initiator and a binder for heating and mixing, forming a crosslinking network structure, and preparing a sulfide solid electrolyte membrane.

Benefits of technology

It improves the mechanical strength and chemical stability of the sulfide solid electrolyte membrane, and enhances the ionic conductivity and overall performance of all-solid state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120413769A_ABST
    Figure CN120413769A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a preparation method of a sulfide solid electrolyte membrane and a product, and relates to the technical field of batteries. The method comprises the following steps: uniformly mixing a sulfide electrolyte, a multi-sulfydryl material and a solvent to obtain first slurry, then adding an initiator and a binder into the first slurry, heating and mixing to obtain second slurry, finally coating a substrate with the slurry, and drying to obtain the sulfide solid electrolyte membrane. Through the method, the prepared sulfide solid electrolyte membrane has relatively good mechanical strength, so that the sulfide solid electrolyte membrane has relatively high performance and reliability when being applied to an all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a preparation method and product of a sulfide solid electrolyte membrane. Background Art

[0002] The rapid development of portable electronic devices, electric vehicles, and renewable energy storage systems is driving increasing demand for high-performance batteries. Compared to traditional lithium-ion batteries, solid-state batteries offer improved safety, higher energy and power densities, and a wider operating temperature range. Sulfide-based all-solid-state batteries, in particular, have attracted significant attention due to the high ionic conductivity and ease of processing of sulfide solid electrolytes.

[0003] Existing sulfide solid electrolyte membrane preparation technologies typically use weakly polar binders to reduce their impact on the chemically unstable sulfide solid electrolyte. However, the poor adhesion of weakly polar binders results in insufficient mechanical strength of the sulfide solid electrolyte membrane, making it difficult to meet the mechanical performance requirements of high-performance all-solid-state batteries.

[0004] In summary, how to improve the mechanical strength of sulfide solid electrolyte membrane has become a technical problem that needs to be solved urgently. Summary of the Invention

[0005] The embodiments of the present application provide a method for preparing a sulfide solid electrolyte membrane and a product, which are used to improve the mechanical strength of the sulfide solid electrolyte membrane, thereby improving the performance and processing yield of all-solid-state batteries.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a sulfide solid electrolyte membrane, comprising:

[0007] uniformly mixing the sulfide electrolyte, the polythiol material and the solvent to obtain a first slurry;

[0008] adding an initiator and a binder to the first slurry, heating and mixing the mixture, to obtain a second slurry;

[0009] The second slurry is coated on a substrate and dried to obtain a sulfide solid electrolyte membrane.

[0010] In a possible embodiment, the step of adding an initiator and a binder to the first slurry and heating and mixing the mixture to obtain a second slurry comprises:

[0011] Mixing and dissolving the binder and the solvent to obtain a glue solution;

[0012] The initiator and the glue are added to the first slurry, and the mixture is heated and mixed to obtain the second slurry.

[0013] In a possible implementation, the multi-mercapto material is a polythiol compound having at least 2 mercapto groups.

[0014] In a possible implementation, the polythiol compound includes:

[0015] At least one of 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 2,6-naphthalenedithiol, toluene-3,4-dithiol, biphenyl-4,4'-dithiol, 4,4'-dimercapto diphenyl sulfide, ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,7-heptanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,11-undecanedithiol, 1,12-dodecanedithiol, 1,13-tridecanedithiol, 1,2-butanedithiol, 2,2'-thiobis(ethanethiol), 3,7-dithia-1,9-nonanedithiol, 1,6-dimercapto-3-hexyl sulfide.

[0016] In a possible implementation, the initiator includes:

[0017] At least one of azobisisobutyronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, tris(pentafluorophenyl)borane, dimethylphenylphosphine, tributylphosphine, triisopropylphosphine, tribenzylphosphine, tricyclopentylphosphine, tris(dimethylamino)phosphine, tripyrrolidinophosphine, tri-n-octylphosphine, anisole, benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoyl peroxide, tert-butyl peroxybenzoate, methyl ethyl ketone peroxide, benzophenone, 2,4-dihydroxybenzophenone, thio-propoxy thioxanthone, 2-isopropyl thioxanthone.

[0018] In a possible implementation, the binder includes:

[0019] At least one of natural rubber, styrene-butadiene rubber, cis-1,4-polybutadiene rubber, nitrile rubber, isoprene rubber, chloroprene rubber, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer.

[0020] In a possible implementation, the solvent includes at least one of aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, ester solvents, ether solvents, and cycloalkane solvents.

[0021] In a possible implementation, the aliphatic hydrocarbon solvent includes at least one of pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, tridecane; [[ID=2,6]]

[0022] The aromatic hydrocarbon solvent includes at least one of benzene, toluene, p-xylene, mesitylene, ethylbenzene, tert-butylbenzene;

[0023] The ester solvent includes at least one of methyl acetate, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, and benzyl acetate;

[0024] The ether solvent includes at least one of dibutyl ether, diamyl ether, anisole, diethylene glycol diethyl ether, and cyclopentyl methyl ether;

[0025] The cycloalkane solvent includes cyclohexane and / or methylcyclohexane.

[0026] In one possible embodiment, the sulfide electrolyte is Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li7P3S 11 、Li2S-P2S5、Li 7-a PS 6-a X a At least one of, wherein X is at least one of Cl, Br, and I, and the value of a is 0.5-2.

[0027] In one possible embodiment, the mass of the initiator accounts for 0.1%-1.5% of the mass of the polythiol material;

[0028] And / or, the mass of the polythiol material accounts for 1%-20% of the mass of the sulfide electrolyte;

[0029] And / or, the mass of the sulfide electrolyte accounts for 90%-99.9% of the mass of the sulfide solid electrolyte membrane;

[0030] And / or, the mass of the binder accounts for 0.1%-10% of the mass of the sulfide solid electrolyte membrane;

[0031] and / or, the particle size of the sulfide electrolyte is 1 μm-200 μm;

[0032] And / or, the sulfide solid electrolyte membrane has a thickness of 10 μm-100 μm.

[0033] In a possible embodiment, during the preparation of the sulfide solid electrolyte membrane, the materials may be mixed by at least one of a mechanical stirrer, a magnetic stirrer, a ball mill, and a thinky.

[0034] In one possible embodiment, when heating and mixing, the heating temperature is 50° C.-80° C., and the heating time is 1 min-30 min;

[0035] And / or, during the drying process, the drying temperature is 60° C.-100° C., and the drying time is 1 hour-20 hours.

[0036] In a second aspect, an embodiment of the present application provides a sulfide solid electrolyte membrane, which is prepared by the method according to any possible one of the first aspect.

[0037] In a third aspect, an embodiment of the present application provides a all-solid-state battery, including: a positive electrode, a negative electrode, and the sulfide solid electrolyte membrane described in the second aspect.

[0038] The preparation method and product of the sulfide solid electrolyte membrane provided by the embodiment of the present application are as follows: by uniformly mixing a sulfide electrolyte, a multi-mercapto material, and a solvent to obtain a first slurry, then adding an initiator and a binder to the first slurry for heating and mixing to obtain a second slurry, and finally coating the slurry on a substrate and performing a drying treatment to obtain the sulfide solid electrolyte membrane. Through the above method, the prepared sulfide solid electrolyte membrane has good mechanical strength, making the application of the sulfide solid electrolyte membrane in the all-solid-state battery have higher performance and reliability. Description of the Drawings

[0039] The drawings herein are incorporated into the specification and form a part of the specification, showing embodiments consistent with the present application, and are used together with the specification to explain the principles of the present application.

[0040] Figure 1 It is a schematic flow chart of a method for preparing a sulfide solid electrolyte membrane provided by the present application.

[0041] Through the above drawings, the specific embodiments of the present application have been shown, and there will be more detailed descriptions hereinafter. These drawings and text descriptions are not intended to limit the scope of the concept of the present application in any way, but to explain the concept of the present application to those skilled in the art by referring to specific embodiments. Detailed Embodiments

[0042] Here, the exemplary embodiments will be described in detail, and the examples are shown in the drawings. When the following description refers to the drawings, unless otherwise indicated, the same numerals in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.

[0043] First, the application background of the present application is explained as follows:

[0044] With the rapid development of portable electronic devices, electric vehicles, and renewable energy storage systems, the demand for high-performance batteries is increasing day by day. Although traditional lithium-ion batteries perform well in terms of energy density and cycle life, their liquid electrolytes are usually composed of organic solvents and lithium salts, making the batteries prone to catching fire or exploding in case of overcharging, short circuit, or mechanical damage. There is also a problem of liquid leakage in liquid electrolytes, which easily reacts with electrode materials to cause side reactions, resulting in the degradation of electrode materials and the attenuation of battery capacity.

[0045] Solid-state batteries have higher safety, greater energy density and power density, and a wider operating range compared to traditional lithium-ion batteries. In particular, sulfide-based all-solid-state batteries have attracted much attention due to the high ionic conductivity (~10 -2 S cm -1 ) of sulfide electrolytes, easy processability, good mechanical properties, and the ability to closely contact electrode materials to reduce the interfacial resistance.

[0046] In the existing preparation technology of sulfide electrolyte membranes, non-polar or weakly polar binders are usually used to reduce the influence of binders on sulfide electrolytes with poor chemical stability. A weakly polar binder refers to a binder material with a relatively low polarity in its molecular structure, which is relatively inert chemically and not easily reacts with other chemical substances. Sulfide electrolytes usually have high chemical activity and are prone to adverse reactions with substances with stronger polarity, thus affecting their performance and stability. By using weakly polar binders, the interaction between the binder and the sulfide electrolyte is reduced, and adverse chemical reactions are minimized, thereby maintaining the chemical stability of the electrolyte. However, the adhesion of weakly polar binders is poor, resulting in insufficient mechanical strength and structural integrity of the sulfide electrolyte membrane, and problems such as cracking and material shedding are likely to occur during the processing, making it difficult to meet the requirements of high-performance all-solid-state batteries for the mechanical properties of the electrolyte membrane.

[0047] In summary, how to improve the mechanical strength of sulfide solid-state electrolyte membranes has become a technical problem to be solved urgently.

[0048] Based on the above technical problems, during the research on the preparation method of sulfide solid-state electrolyte membranes, the inventors found that by introducing multi-mercapto materials and initiators during the preparation of sulfide solid-state electrolytes, a cross-linked network structure can be formed, thereby improving the mechanical strength of sulfide solid-state electrolytes. Based on this, the present application provides a preparation method and product of a sulfide solid-state electrolyte membrane.

[0049] The following uses specific examples to elaborate in detail on the technical solutions of the present application and how the technical solutions of the present application solve the above technical problems. These specific examples below can be combined with each other, and the same or similar concepts or processes may not be repeated in some examples. The following will describe the embodiments of the present application with reference to the accompanying drawings.

[0050] Figure 1 The flowchart of a preparation method of a sulfide solid electrolyte membrane provided for this application is shown as Figure 1 follows. The method includes:

[0051] S101: Mix the sulfide electrolyte, the multi-mercapto material, and the solvent evenly to obtain a first slurry.

[0052] In this step, the sulfide electrolyte is a type of material used in solid-state batteries, composed of sulfur elements and other metal or semi-metal elements, and has high ionic conductivity. The multi-mercapto material refers to a compound containing multiple mercapto (-SH groups), and the mercapto is a sulfur-containing functional group with high reactivity. The solvent is used to dissolve other substances, help disperse the materials evenly, and form a slurry or solution.

[0053] In a possible implementation manner, the multi-mercapto material is a polythiol compound having at least 2 mercapto groups.

[0054] In a possible implementation manner, the polythiol compound includes at least one of: 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 2,6-naphthalenedithiol, toluene-3,4-dithiol, biphenyl-4,4'-dithiol, 4'4-dimercapto diphenyl sulfide, ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,7-heptanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,11-undecanedithiol, 1,12-dodecanedithiol, 1,13-tridecanedithiol, 1,2-butanedithiol, 2,2'-thiobis(ethanethiol), 3,7-dithia-1,9-nonanedithiol, 1,6-dimercapto-3-hexyl sulfide.

[0055] Multiple mercapto groups in the multi-mercapto material can undergo cross-linking reactions with other compounds to form a stable three-dimensional network structure. Taking 1,11-undecanedithiol as an example, 1,11-undecanedithiol belongs to the polythiol compound, and its molecular structure contains two mercapto (-SH) functional groups. Specifically, the two mercapto groups are located at both ends of the undecane chain, making it a linear dithiol. 1,11-undecanedithiol containing two mercapto groups has high chemical reactivity and can undergo cross-linking reactions with other compounds to form a stable three-dimensional network structure. In addition, the relatively long carbon chain of 1,11-undecanedithiol gives the material certain flexibility and ductility, so the prepared sulfide solid electrolyte membrane also has good integrity and adaptability.

[0056] In a possible implementation manner, the solvent includes at least one of: aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, ester solvents, ether solvents, and cycloalkane solvents.

[0057] Aliphatic hydrocarbon solvents are chain or branched compounds composed of carbon and hydrogen, usually non-polar, with good solubility, used to dissolve oils and other non-polar substances, and have low boiling points and volatility. Aromatic hydrocarbon solvents contain one or more benzene rings, have high solubility, and are especially suitable for dissolving polar or aromatic compounds. Ester solvents are compounds formed by the reaction of acids and alcohols, have good solubility and volatility, and are commonly used in the paint and ink industries. Ether solvents are composed of an oxygen atom connecting two hydrocarbon groups, have medium polarity, and can dissolve a variety of organic substances. Naphthenic hydrocarbon solvents are composed of saturated cyclic hydrocarbons, have high chemical stability and solubility, and are commonly used in paints and cleaning agents.

[0058] In one possible embodiment, the aliphatic hydrocarbon solvent includes at least one of pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, tridecane;

[0059] The aromatic hydrocarbon solvent includes at least one of benzene, toluene, p-xylene, mesitylene, ethylbenzene, tert-butylbenzene;

[0060] The ester solvent includes at least one of methyl acetate, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, benzyl acetate;

[0061] The ether solvent includes at least one of dibutyl ether, dipentyl ether, anisole, diethylene glycol diethyl ether, cyclopentyl methyl ether;

[0062] The naphthenic hydrocarbon solvent includes cyclohexane and / or methylcyclohexane.

[0063] Taking hexane in the aliphatic hydrocarbon solvent as an example, hexane is a common aliphatic hydrocarbon solvent with the chemical formula C6H 14 , is a colorless, low-boiling, volatile non-polar liquid with a slight odor. Hexane has good solubility and is especially suitable for dissolving non-polar substances such as oils, waxes, and resins. Due to the volatility and potential health risks of hexane, attention should be paid to ventilation and safety protection during use to avoid inhaling high concentrations of vapors.

[0064] Taking p-xylene in the aromatic hydrocarbon solvent as an example, p-xylene is a colorless and transparent liquid with an aromatic odor, flammable and volatile, and its chemical formula is C8H 10, is one of the three isomers of xylene, having a benzene ring structure with two methyl CH3 groups located para (i.e., on opposite carbon atoms). p-Xylene is widely used in industry for the production of terephthalic acid and is an important raw material for manufacturing polyethylene terephthalate plastics and fibers. Due to the volatility and potential health effects of p-xylene, appropriate safety measures such as good ventilation and personal protective equipment should be taken when using it to avoid inhaling high concentrations of vapors or contacting the skin.

[0065] Taking ethyl acetate in ester solvents as an example, ethyl acetate is a colorless and transparent liquid with a sweet fruity smell and high volatility, and its chemical formula is C4H8O2. Ethyl acetate is an ester compound formed by the reaction of acetic acid and ethanol in the presence of an acid catalyst, having good solubility and relatively low toxicity. Due to its flammability and volatility, fire prevention measures should be taken when using ethyl acetate, and good ventilation of the working environment should be ensured to avoid inhaling high concentrations of vapors.

[0066] Taking dibutyl ether in ether solvents as an example, dibutyl ether is a colorless liquid with the typical smell of ether substances, and its chemical formula is C8H 18 O. Dibutyl ether is composed of two butyl groups connected by an oxygen atom and belongs to a symmetrical ether, having low polarity, low toxicity and high volatility. However, it may form explosive peroxides when exposed to air for a long time. Therefore, peroxide detection can be carried out in advance when using and storing dibutyl ether, and long-term exposure to air should be avoided.

[0067] Taking cyclohexane in cycloalkane solvents as an example, cyclohexane is a colorless and transparent liquid with a slight sweet smell and the typical smell of hydrocarbons, and its chemical formula is C6H 12 , cyclohexane is a cyclic structure composed of six carbon atoms, with two hydrogen atoms connected to each carbon atom. Its non-polar nature and chemical inertness enable it to dissolve a variety of non-polar compounds. Cyclohexane has relatively low toxicity, flammability and volatility, and its vapor can form an explosive mixture with air. Therefore, fire sources and high-temperature environments should be avoided during use and storage.

[0068] In a possible implementation, the sulfide electrolyte is Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li7P3S 11 、Li2S-P2S5、Li 7-a PS 6-a X a at least one of them, where X is at least one of Cl, Br, I, and the value of a is 0.5 - 2.

[0069] Li10 GeP2S 12 ,Lithium germanium thiophosphate is a sulfide electrolyte with high lithium-ion conductivity, and its conductivity can reach the order of 10-2 S / cm, making it an ideal choice for high-performance solid-state batteries. Li 10 SnP2S 12 ,Lithium tin thiophosphate is a 10 GeP2S 12 analogue of, in which tin is replaced by silicon. Although the conductivity of 10 SnP2S 12 is slightly lower than that of 10 GeP2S 12 , it has advantages in terms of cost and material availability because tin is more abundant and cheaper than germanium. Li7P3S 11 is a sulfide-based solid electrolyte commonly used in all-solid-state lithium-ion batteries. Its crystal structure is conducive to the rapid migration of lithium ions, and it has high chemical stability and ionic conductivity. Li2S-P2S5 is a solid electrolyte material system composed of lithium sulfide and phosphorus pentasulfide, which can form a variety of sulfide glasses or glass ceramics through different molar ratio combinations, and has high ionic conductivity and also has advantages in terms of electrochemical stability and mechanical strength. Li 7-a PS 6-a X a (where X is at least one of Cl, Br, I, and the value of a ranges from 0.5 to 2), is a type of electrolyte called "sulfide halide" or "sulfide-halide mixture". The value of a can be 0.5, 1, 1.5, or 2. By changing the content of halogen elements (such as chlorine, bromine, iodine), the crystal structure and conductivity of the material can be changed. A higher halogen content will cause significant changes in the crystal structure, thereby optimizing the migration path of lithium ions and improving conductivity.

[0070] By uniformly mixing a sulfide electrolyte, a multi-mercapto material, and a solvent, a first slurry can be obtained, which can achieve uniform distribution of the materials and provide a material basis for the subsequent fabrication of a sulfide solid electrolyte membrane.

[0071] S102: Add an initiator and a binder to the first slurry and heat and mix to obtain a second slurry.

[0072] In this step, an initiator is a chemical substance used to initiate a polymerization reaction or a crosslinking reaction. After adding the initiator and activating it by heating or other means, the initiator decomposes to generate free radicals or other reactive species, which initiate the polymerization reaction of monomers or prepolymers to form polymer chains or crosslinked networks. A binder is a substance used to improve the adhesion within the material and between the material and the substrate. Adding a binder can form a continuous phase within the material, provide the necessary adhesion and flexibility, enhance the structural integrity and mechanical strength of the material, and ensure that the material does not delaminate or fall off during processing and use.

[0073] In one possible implementation, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, tris(pentafluorophenyl)borane, dimethylphenylphosphine, tri-n-butylphosphine, triisopropylphosphine, tribenzylphosphine, tricyclopentylphosphine, tris(dimethylamino)phosphine, tripyrrolidinophosphine, tri-n-octylphosphine, anisole, benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoyl peroxide, tert-butyl perbenzoate, methyl ethyl ketone peroxide, benzophenone, 2,4-dihydroxybenzophenone, thio-propoxyxanthone, 2-isopropylxanthone.

[0074] The free radicals or other reactive substances generated by the decomposition of the initiator can initiate the polymerization reaction of monomers or prepolymers, thereby forming polymer chains or crosslinked networks. Taking azobisisobutyronitrile as an example, azobisisobutyronitrile is a white crystalline powder with good solubility and stability, and its chemical formula is C8H 12 N4. The initiation mechanism of azobisisobutyronitrile lies in the azo group (-N=N-) in its molecular structure. This group decomposes to generate nitrogen and two free radicals under heating conditions, and the two free radicals can initiate the polymerization reaction of monomers to form polymer chains. Azobisisobutyronitrile has become an important tool in free radical polymerization due to its high initiation ability and relatively simple operating conditions.

[0075] In one possible implementation, the binder includes at least one of natural rubber, styrene-butadiene rubber, cis-1,4-polybutadiene rubber, nitrile rubber, isoprene rubber, chloroprene rubber, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer.

[0076] Binders improve the adhesion within a material and between it and its substrate, enhancing the material's structural integrity and mechanical strength. They are characterized by chain segments containing a C=C structure. For example, natural rubber, primarily made from latex from rubber trees, is primarily composed of cis-1,4-polyisoprene, which possesses excellent elasticity, strength, and wear resistance. Using natural rubber as a binder effectively improves the material's structural integrity and durability. It forms a continuous phase within the material, strengthening adhesion between particles and preventing delamination or shedding during use.

[0077] By adding an initiator and a binder to the first slurry and heating and mixing them, a polymerization or cross-linking reaction is initiated, forming a polymer chain or cross-linked network within the material, significantly improving the mechanical strength and thermal stability of the material. Specifically, the thiol groups of the polythiol material in S101 first react with sulfur atoms on the surface of the sulfide electrolyte to form SS bonds. The initiator is thermally cracked and reacts with the remaining thiol groups in the polythiol material to form thiol free radicals. The thiol free radicals react with the carbon double bond C=C of the binder to form a free radical intermediate, which then captures the hydrogen atom of another thiol group to achieve chemical bonding between the electrolyte and the binder. The stable chemical bonding between the sulfide electrolyte and the binder can significantly improve the mechanical strength of the sulfide electrolyte membrane, thereby reducing the amount of binder used, increasing the ionic conductivity of the sulfide electrolyte membrane, and improving the performance of all-solid-state batteries. In addition, by bonding the polythiol material to the surface of the sulfide electrolyte particles, the carbon chains of the polythiol material can form a hydrophobic layer on the surface of the sulfide electrolyte, improving the stability of the sulfide electrolyte in air.

[0078] S103: coating the second slurry on the substrate and drying it to obtain a sulfide solid electrolyte membrane.

[0079] In this step, the solvent in the second slurry coated on the substrate is removed by a drying method such as heating, natural evaporation, or vacuum drying, so that the remaining solid components form a continuous solid film, namely, a sulfide solid electrolyte membrane.

[0080] In a possible embodiment, during the drying process, the drying temperature is 60° C.-100° C., and the drying time is 1 hour-20 hours.

[0081] Through heat drying treatment, the solvent in the second slurry coated on the substrate evaporates, and the remaining solid components form a continuous solid film. A lower drying temperature can reduce the risk of thermal degradation of heat-sensitive materials, and low-temperature drying is usually used to protect the chemical integrity and physical properties of the materials; a higher drying temperature can accelerate the evaporation of the solvent, improve the drying efficiency, and shorten the drying time. However, an excessively high temperature may cause thermal degradation of the materials or trigger chemical side reactions; a shorter drying time is suitable for the case of rapid evaporation of the solvent and is usually combined with a higher drying temperature; a longer drying time is usually combined with a lower drying temperature to ensure the complete evaporation of the solvent. Among them, the drying temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, etc., and the drying time can be 1 h, 5 h, 10 h, 15 h, 18 h, 20 h, etc., to ensure the rapid evaporation of the solvent without thermal degradation. The specific values of the drying temperature and drying time here are only for illustration, and should be appropriately adjusted in actual applications.

[0082] By coating the second slurry on the substrate, the obtained sulfide solid electrolyte film after drying treatment has high mechanical strength, chemical stability, and ionic conductivity.

[0083] The method for preparing a sulfide solid electrolyte film provided by the embodiments of the present application. In this method, first, a sulfide electrolyte, a multi-mercapto material, and a solvent are mixed evenly to prepare a first slurry. Then, an initiator and a binder are added to the first slurry, and the second slurry is formed by heating and mixing. Finally, the second slurry is coated on the substrate and dried to remove the solvent, forming a continuous sulfide solid electrolyte film. Through the above method, the multi-mercapto material forms mercapto groups under the action of the initiator, and can respectively form bonds with sulfur in the sulfide electrolyte and the carbon-carbon double bond C=C structure in the binder, improving the bonding strength between the sulfide electrolyte and the binder, and further improving the mechanical strength of the sulfide electrolyte film. Therefore, the prepared sulfide solid electrolyte film exhibits excellent mechanical strength and chemical stability, and can provide efficient ionic conduction performance in all-solid-state batteries. In addition, through chemical bonding and the formation of a surface hydrophobic layer, the stability of the sulfide solid electrolyte film in air is also significantly improved, enhancing the ionic conductivity and improving the overall performance of the all-solid-state battery.

[0084] In Figure 1 Based on the embodiment, in S102, adding an initiator and a binder to the first slurry for heating and mixing to obtain the second slurry specifically further includes:

[0085] In a possible implementation manner, the binder is mixed and dissolved with the solvent to obtain a glue solution.

[0086] Through the action of the solvent, the binder can be transformed from a solid state or a high-viscosity state into a more easily processable liquid state or low-viscosity state. In addition, the solvent can help the binder form a uniform thin film on the substrate surface, improving the bonding strength and stability. By mixing and dissolving the binder with the solvent, not only the fluidity and coatability of the binder are improved, but also the curing rate of the binder can be controlled to adapt to different application requirements and environmental conditions.

[0087] In a possible implementation, an initiator and a glue solution are added to the first slurry and heated and mixed to obtain a second slurry.

[0088] As described in S102, by adding an initiator and a binder (a glue solution obtained by mixing the binder with a solvent) to the first slurry and heating and mixing, a polymerization or cross-linking reaction is initiated to form polymer chains or a cross-linking network inside the material, improving the mechanical strength and thermal stability of the material.

[0089] In Figure 1 Based on the embodiment, in S101, a sulfide electrolyte, a multi-mercapto material, and a solvent are mixed evenly to obtain a first slurry, specifically including:

[0090] In a possible implementation, the particle size of the sulfide electrolyte is 1 μm - 200 μm.

[0091] The smaller the particle size of the sulfide electrolyte, the more conducive it is to increasing the specific surface area of the electrolyte, improving the contact area between the electrolyte and the electrode material, thereby increasing the number and efficiency of ion conduction paths and enhancing the ionic conductivity and overall performance of the battery. However, too small a particle size may cause particle agglomeration, affecting the uniformity and processability of the electrolyte. On the contrary, a larger particle size of the sulfide electrolyte can provide better mechanical strength and stability. However, too large a particle size may reduce the ionic conductivity of the electrolyte. Specifically, the particle size of the sulfide electrolyte can be 1 μm, 50 μm, 100 μm, 150 μm, 180 μm, 200 μm, etc. The specific values of the particle size here are only for illustrative purposes, and can be adjusted appropriately according to actual needs in practical applications.

[0092] In Figure 1 Based on the embodiment, in S102, an initiator and a binder are added to the first slurry and heated and mixed to obtain a second slurry, specifically including:

[0093] In a possible implementation, when performing the heating and mixing, the heating temperature is 50°C - 80°C, and the heating time is 1 min - 30 min.

[0094] Heating and mixing are used to accelerate the rate of chemical reactions, enabling the components in the first slurry to react with the initiator and binder more quickly to form the desired compounds. A lower heating temperature can gently promote the decomposition of the initiator and the dissolution of the binder, thereby forming a uniform slurry; a higher heating temperature can accelerate the decomposition of the initiator and the reaction rate, quickly forming the desired chemical structure, but an excessively high heating temperature may increase the risk of side reactions or cause the degradation of some heat-sensitive materials. A shorter heating time is suitable for a rapid reaction system, which can effectively reduce energy consumption and time costs; a longer heating time helps to ensure the complete progress of the reaction. Specifically, the heating temperature can be 50°C, 60°C, 70°C, 75°C, 80°C, etc., and the heating time can be 1 min, 5 min, 10 min, 20 min, 25 min, 30 min, etc. The specific values of the heating temperature and time here are only for illustration. In actual applications, they should be adjusted appropriately according to actual needs to achieve the best material properties and production efficiency.

[0095] Based on Figure 1 the embodiments, in S101 - S103, the preparation method of the sulfide solid electrolyte membrane specifically further includes:

[0096] In a possible implementation manner, the mass of the sulfide electrolyte accounts for 90% - 99.9% of the mass of the sulfide solid electrolyte membrane

[0097] The mass of the sulfide solid electrolyte membrane directly affects its thickness and uniformity, mechanical strength and flexibility, as well as the overall weight and volume of the battery. Assuming that it is now necessary to prepare a sulfide solid electrolyte membrane with a mass fraction of 1, then the mass fraction of the sulfide electrolyte can be 0.9, 0.93, 0.95, 0.97, 0.99, etc. Of course, the specific values of the mass fraction of the sulfide electrolyte here are only for illustration. In actual applications, they should be adjusted appropriately according to the actual preparation requirements of the sulfide electrolyte membrane, and this application does not make specific limitations.

[0098] In a possible implementation manner, the mass of the binder accounts for 0.1% - 10% of the mass of the sulfide solid electrolyte membrane.

[0099] A binder is a substance that can improve the adhesion inside the material and between the material and the substrate, enhancing the structural integrity and mechanical strength of the material. As described in the previous embodiment, assuming that it is now necessary to prepare a sulfide electrolyte membrane with a mass fraction of 1, then the mass fraction of the binder can be 0.001, 0.01, 0.05, 0.07, 0.1, etc. Of course, the specific values of the mass fraction of the binder here are only for illustration. In actual applications, they should be adjusted appropriately according to the actual preparation requirements of the sulfide electrolyte membrane, and this application does not make specific limitations.

[0100] In a possible embodiment, during the preparation of the sulfide solid electrolyte membrane, the materials may be mixed by at least one of a mechanical stirrer, a magnetic stirrer, a ball mill, and a thinky.

[0101] During the preparation of sulfide solid electrolyte membranes, at least one of a mechanical mixer, magnetic mixer, ball mill, or thinky mixer is used to achieve uniform mixing of materials through mechanical motion, ensuring consistent component distribution. For example, the thinky mixer is a planetary centrifugal mixing device that utilizes centrifugal and shear forces for contactless mixing of materials. Using the thinky mixer enables efficient and uniform mixing in a short time, increasing the preparation rate of sulfide solid electrolyte membranes.

[0102] In a possible implementation, the thickness of the sulfide solid electrolyte membrane is 10 μm-100 μm.

[0103] In a specific implementation of this solution, the thickness of the sulfide solid electrolyte membrane is 10μm-100μm, and its thickness can be 10μm, 30μm, 50μm, 70μm, 100μm, etc., wherein a thinner sulfide solid electrolyte membrane means that its mass is also smaller, which can significantly reduce the length of the ion transmission path, thereby reducing the internal resistance and improving the power density and efficiency of the battery. However, a sulfide solid electrolyte membrane that is too thin may be insufficient in mechanical strength and durability, and easily lead to physical damage or short circuit risks. On the contrary, a thicker sulfide solid electrolyte membrane means that its mass is also larger, and generally has higher mechanical strength and resistance, and can better withstand the mechanical stress during battery assembly and operation. However, an overly thick sulfide solid electrolyte membrane may increase the length of the ion transmission path, thereby increasing the internal resistance and reducing the energy density and efficiency of the battery. Of course, the specific value of the thickness of the sulfide solid electrolyte membrane here is only for example. In actual application, it should be appropriately adjusted according to the actual preparation requirements of the sulfide electrolyte membrane, and this application does not make specific limitations.

[0104] In one possible embodiment, the mass of the polythiol material accounts for 1%-20% of the mass of the sulfide electrolyte.

[0105] The multiple thiol groups in polythiol materials can cross-link with other compounds to form a stable three-dimensional network structure, which can effectively improve the ionic conductivity and interfacial stability of the electrolyte, thereby enhancing the overall battery performance. By adjusting the proportion of polythiol materials, the mechanical properties and chemical stability of the electrolyte can be optimized and side reactions between the electrolyte and the electrode materials can be reduced.

[0106] As described in the above embodiments, assuming that a sulfide solid electrolyte membrane with a mass fraction of 1 needs to be prepared, the mass fraction of the sulfide electrolyte can be 0.9, and the mass of the multi-mercapto material accounts for 1%-20% of the mass of the sulfide electrolyte. That is to say, when the mass fraction of the sulfide electrolyte is 0.9, the mass fractions of the multi-mercapto material can be 0.009, 0.045, 0.09, 0.135, 0.162, 0.18, etc. More multi-mercapto materials can form a denser cross-linked network, which helps to improve the mechanical strength and interfacial stability of the sulfide electrolyte membrane, while enhancing the ionic conductivity. However, too much multi-mercapto material may lead to a decrease in the flexibility of the sulfide electrolyte membrane, affecting its adaptability in some applications. On the contrary, although the degree of cross-linking is lower with less multi-mercapto material, the flexibility and processability of the sulfide electrolyte membrane may be better, which is suitable for application scenarios that require higher flexibility. However, too little multi-mercapto material may not be sufficient to significantly improve the ionic conductivity and interfacial stability of the sulfide electrolyte membrane. Therefore, in practical applications, it is necessary to select an appropriate proportion of the multi-mercapto material according to the specific battery design requirements and performance requirements to balance the conductivity, mechanical properties and chemical stability of the sulfide electrolyte membrane.

[0107] In a possible implementation manner, the mass of the initiator accounts for 0.1%-1.5% of the mass of the multi-mercapto material.

[0108] The free radicals or other active substances generated by the decomposition of the initiator can initiate the polymerization reaction of monomers or prepolymers, thereby forming polymer chains or cross-linked networks.

[0109] As described in the above embodiments, assuming that a sulfide solid electrolyte membrane with a mass fraction of 1 needs to be prepared, then the mass fraction of the sulfide electrolyte can be 0.9, and the mass fraction of the multi-mercapto material can be 0.18. The mass of the initiator accounts for 0.1%-1.5% of the mass of the multi-mercapto material. That is to say, when the mass fraction of the multi-mercapto material is 0.18, the mass fraction of the initiator can be 0.00018, 0.0009, 0.0018, 0.00234, 0.027, etc. When the content of the initiator is relatively high, the number of free radicals or other active substances generated by it increases, accelerating the rate of the polymerization reaction, and the rapidly formed polymer chains or crosslinked networks are relatively dense, which helps to improve the mechanical strength and thermal stability of the material. However, too much initiator may cause the reaction to be too violent, generating too much heat, which may trigger side reactions or increase the brittleness of the material. On the contrary, when the content of the initiator is low, the rate of the polymerization reaction will slow down, and the formed polymer chains or crosslinked networks are relatively sparse, which may lead to a decrease in the mechanical properties and thermal stability of the material, but at the same time ensure good flexibility and ductility of the sulfide solid electrolyte membrane. Therefore, in practical applications, it is necessary to select an appropriate initiator ratio according to specific battery design requirements and performance requirements to balance the flexibility and mechanical strength of the sulfide solid electrolyte membrane.

[0110] The present application also provides a sulfide solid electrolyte membrane, which is prepared by the Figure 1 method described in the embodiments.

[0111] The present application also provides a all-solid-state battery, including: a positive electrode, a negative electrode, and the sulfide solid electrolyte membrane described in the previous embodiment.

[0112] The present application also provides an electrical device, including a device main body and the all-solid-state battery described in the previous embodiment.

[0113] Exemplarily, the all-solid-state battery can be used as a power battery of a vehicle to provide a power source for the vehicle. In addition, the all-solid-state battery is also used in the fields of batteries for computers, communications, and consumer electronics (3C), and can also be used in aircraft or drones, etc., to provide stable and lasting power support for them.

[0114] Hereinafter, specific embodiments will be used to specifically introduce the preparation method of the sulfide solid electrolyte membrane provided by the present application and the application of the product.

[0115] Unless otherwise specified, the reagents, materials, and instruments used in the following embodiments are all conventional reagents, conventional materials, and conventional instruments in the art, and can all be obtained through commercial purchase. The reagents involved can also be obtained by conventional methods in the art.

[0116] In the following examples and comparative examples, the method for testing the peel strength is as follows: Cut the above-mentioned sulfide solid electrolyte membrane into strips with a size of 10 mm × 150 mm, then bond it to a stainless steel plate with a much larger area than the sample through double-sided tape, roll it back and forth 5 times horizontally at a rate of 10 mm / s with a 2 kg roller, then remove the electrolyte membrane substrate, paste the tape on the other side of the sulfide solid electrolyte membrane, and finally fix the test sample in the fixture of the instrument (universal tensile machine). The peeling rate is 300 mm / min, and the peeling force test is completed to obtain the peel strength.

[0117] The method for testing the ionic conductivity is as follows: Place a sulfide solid electrolyte membrane with a diameter of 10 mm in the test mold. After assembly, apply a pressure of 600 MPa to the mold, connect the test fixture, and test its AC impedance at room temperature. After the AC impedance test is completed, measure the thickness H of the sulfide solid electrolyte membrane and the area S of the electrolyte membrane after removing the pressure of the mold. The calculation method for the conductivity is: σ = H / R·S, where the intersection point of the curve and the X-axis is the resistance R.

[0118] Example 1

[0119] This example provides a sulfide solid electrolyte membrane, and its preparation method includes the following steps:

[0120] (1) Mix 9.5 g of sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 with a particle size of 5 μm, 0.95 g of multi-mercapto material 1,11-undecanedithiol, and 7.0 g of solvent p-xylene evenly through a thinky mixer to obtain the first slurry;

[0121] (2) Mix and dissolve 0.1 g of binder nitrile rubber with 1.44 g of solvent p-xylene to obtain a glue solution;

[0122] (3) Add 0.01 g of initiator azobisisobutyronitrile and the glue solution obtained in step (2) to the first slurry obtained in step (1), and heat and mix. The heating temperature is 60 °C and the heating time is 10 min to obtain the second slurry;

[0123] (4) Coat the second slurry obtained in step (3) on the substrate, and after drying treatment, obtain a sulfide solid electrolyte membrane with a thickness of 50 μm. Among them, the drying temperature is 80 °C and the drying time is 14 h.

[0124] Example 2

[0125] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the multi-mercapto material in step (1) is 1,9-nonanedithiol.

[0126] Example 3

[0127] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the polythiol material in step (1) is 2,2'-thiobis(ethanethiol).

[0128] Example 4

[0129] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the amount of the multimercapto material 1,11-undecanedithiol used in step (1) is 0.48 g.

[0130] Example 5

[0131] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the amount of the multimercapto material 1,11-undecanedithiol used in step (1) is 1.43 g.

[0132] Example 6

[0133] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that the binder in step (2) is styrene-butadiene rubber.

[0134] Example 7

[0135] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that the binder in step (2) is a styrene-butadiene-styrene block copolymer.

[0136] Example 8

[0137] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that the amount of the binder nitrile rubber used in step (2) is 0.2 g.

[0138] Example 9

[0139] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that the amount of the binder nitrile rubber used in step (2) is 0.3 g.

[0140] Example 10

[0141] This embodiment provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that the initiator in step (3) is tert-butyl perbenzoate.

[0142] Example 11

[0143] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the sulfide electrolyte in step (1) is L6PS5Cl.

[0144] Example 12

[0145] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the particle size of the sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 in step (1) is 3 μm.

[0146] Example 13

[0147] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the particle size of the sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 in step (1) is 7 μm.

[0148] Example 14

[0149] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1, except that: the heating temperature in step (3) is 50 °C and the heating time is 20 min, and the drying temperature in step (4) is 60 °C and the drying time is 18 h.

[0150] Comparative Example 1

[0151] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1. The main difference is that: no multi-mercapto material and initiator are added, and it specifically includes the following steps:

[0152] (1) Mix and dissolve 0.1 g of binder nitrile rubber with 1.44 g of solvent p-xylene to obtain a glue solution;

[0153] (2) Mix 9.5 g of sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 with a particle size of 5 μm, the glue solution obtained in step (1), and 6.23 g of solvent p-xylene uniformly through a thinky mixer to obtain a first slurry;

[0154] (3) Coating the first slurry obtained in step (2) on a substrate, and obtaining a sulfide solid electrolyte membrane with a thickness of 50 μm after drying treatment. Among them, the drying temperature is 80 °C and the drying time is 14 h.

[0155] Comparative Example 2

[0156] This example provides a sulfide solid electrolyte membrane, and its preparation method is basically the same as that of Example 1. The main difference is that no initiator is added. The specific steps are as follows:

[0157] (1) Mix 9.5 g of sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 , 0.95 g of multi-mercapto material 1,11-undecanedithiol, and 7.0 g of solvent p-xylene uniformly through a thinky mixer to obtain a first slurry;

[0158] (2) Mix and dissolve 0.1 g of binder nitrile rubber with 1.45 g of solvent p-xylene to obtain a glue solution;

[0159] (3) Add the glue solution in step (2) to the first slurry obtained in step (1) and heat and mix. The heating temperature is 60 °C and the heating time is 10 min to obtain a second slurry;

[0160] (4) Coat the second slurry obtained in step (3) on a substrate, and after drying, a sulfide solid electrolyte membrane with a thickness of 50 μm is obtained. Among them, the drying temperature is 80 °C and the drying time is 14 h.

[0161] Test Example

[0162] Perform the following performance tests on the sulfide solid electrolyte membranes in the above examples and comparative examples:

[0163] (1) Peel strength test method: Cut the above sulfide solid electrolyte membrane into strips with a size of 10 mm × 150 mm, then bond it to a stainless steel plate with an area much larger than the sample through double-sided tape, roll it back and forth 5 times horizontally at a rate of 10 mm / s with a 2 kg roller, then remove the electrolyte membrane substrate, paste the tape on the other side of the sulfide solid electrolyte membrane, and finally fix the test sample in the fixture of the instrument (universal tensile machine). The peeling rate is 300 mm / min to complete the peeling force test and obtain the peel strength.

[0164] (2) Ion conductivity test method: Place a sulfide solid electrolyte membrane with a diameter of 10 mm in a test mold. After assembly, apply a pressure of 600 MPa to the mold, connect the test fixture, and test its AC impedance at room temperature. After the AC impedance test is completed, measure the thickness H of the sulfide solid electrolyte membrane and the area S of the electrolyte membrane after removing the pressure of the mold. The conductivity calculation method is: σ = H / R·S, where the intersection point of the curve and the X-axis is the resistance R.

[0165] The test results of the peel strength and ionic conductivity are shown in Table 1.

[0166] Table 1 Test Results of Peel Strength and Ionic Conductivity

[0167] Example Peeling strength N / cm Ionic conductivity mS / cm Example 1 0.27 2.7 Example 2 0.25 2.6 Example 3 0.23 2.6 Example 4 0.25 2.8 Example 5 0.28 2.1 Example 6 0.23 2.8 Example 7 0.25 2.6 Example 8 0.29 2.2 Example 9 0.31 1.9 Example 10 0.26 2.5 Example 11 0.26 1.9 Example 12 0.26 2.2 Example 13 0.25 2.8 Example 14 0.26 2.1 Comparative Example 1 0.12 2.8 Comparative Example 2 0.11 2.6

[0168] The following conclusions can be analyzed from Table 1:

[0169] The peel strength of the sulfide solid electrolyte membranes in Examples 1-14 ranges from 0.23 to 0.31 N / cm, while the peel strength of the sulfide solid electrolyte membranes in Comparative Examples 1-2 is only 0.11 to 0.12 N / cm, indicating that the sulfide solid electrolyte membranes in Examples 1-14 have a significant improvement in adhesion. At the same time, the ionic conductivity of the sulfide solid electrolyte membranes in Examples 1-14 is between 1.9 and 2.8 mS / cm, showing good conductive performance. Although the ionic conductivity of the sulfide solid electrolyte membranes in Comparative Examples 1-2 is comparable to that in some examples, due to their lower peel strength, their overall performance is still inferior to that of the sulfide solid electrolyte membranes in Examples 1-14.

[0170] It is further proved that by forming chemical bonds between the multi-mercapto material and the sulfide electrolyte and the binder under the action of the initiator, the mechanical strength of the electrolyte membrane is effectively improved, and the ionic conductivity of the sulfide electrolyte membrane can also be increased by reducing the amount of the binder, thereby improving the performance of the all-solid-state battery.

[0171] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it: Although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: They can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features: And these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a sulfide solid electrolyte membrane, characterized in that, Comprising: Mixing a sulfide electrolyte, a multi-mercapto material, and a solvent uniformly to obtain a first slurry; Adding an initiator and a binder to the first slurry and heating and mixing to obtain a second slurry; Coating the second slurry on a substrate and performing a drying treatment to obtain a sulfide solid electrolyte membrane.

2. The method according to claim 1, wherein The adding an initiator and a binder to the first slurry and heating and mixing to obtain a second slurry includes: Mixing and dissolving the binder with the solvent to obtain a glue solution; Adding the initiator and the glue solution to the first slurry and heating and mixing to obtain the second slurry.

3. The method according to claim 1 or 2, characterized in that, The multi-mercapto material is a polythiol compound having at least 2 mercapto groups.

4. The method according to claim 3, characterized in that, The polythiol compound includes: At least one of 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 2,6-naphthalenedithiol, toluene-3,4-dithiol, biphenyl-4,4'-dithiol, 4,4'-dimercapto diphenyl sulfide, ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,7-heptanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,11-undecanedithiol, 1,12-dodecanedithiol, 1,13-tridecanedithiol, 1,2-butanedithiol, 2,2'-thiobis(ethanethiol), 3,7-dithia-1,9-nonanedithiol, 1,6-dimercapto-3-hexyl sulfide.

5. The method according to claim 1 or 2, characterized in that, The initiator includes: At least one of azobisisobutyronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, tris(pentafluorophenyl)borane, dimethylphenylphosphine, tri-n-butylphosphine, triisopropylphosphine, tribenzylphosphine, tricyclopentylphosphine, tris(dimethylamino)phosphine, tripyrrolidinophosphine, tri-n-octylphosphine, anisole, benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoyl peroxide, tert-butyl peroxybenzoate, and methyl ethyl ketone peroxide, benzophenone, 2,4-dihydroxybenzophenone, thio propoxy thioxanthone, 2-isopropyl thioxanthone.

6. The method according to claim 1 or 2, characterized in that, The binder includes: At least one of natural rubber, styrene-butadiene rubber, cis-1,4-polybutadiene rubber, nitrile rubber, isoprene rubber, chloroprene rubber, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer.

7. The method according to claim 1 or 2, characterized in that, The solvent includes: at least one of aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, ester solvents, ether solvents, and cycloalkane solvents.

8. The method according to claim 7, wherein The aliphatic hydrocarbon solvents include at least one of pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, tridecane; The aromatic hydrocarbon solvents include at least one of benzene, toluene, p-xylene, mesitylene, ethylbenzene, tert-butylbenzene; The ester solvents include at least one of methyl acetate, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, benzyl acetate; The ether solvents include at least one of dibutyl ether, dipentyl ether, anisole, diethylene glycol diethyl ether, cyclopentyl methyl ether; The cycloalkane solvents include cyclohexane and / or methylcyclohexane.

9. The method according to claim 1 or 2, characterized in that The sulfide electrolyte is Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li7P3S 11 , Li2S-P2S5, Li 7-a PS 6-a X a wherein X is at least one of Cl, Br, and I, and the value of a is 0.5-2.

10. The method according to claim 1 or 2, characterized in that, The mass of the initiator accounts for 0.1%-1.5% of the mass of the multi-mercapto material; and / or, the mass of the multi-mercapto material accounts for 1%-20% of the mass of the sulfide electrolyte; and / or, the mass of the sulfide electrolyte accounts for 90%-99.9% of the mass of the sulfide solid electrolyte membrane; and / or, the mass of the binder accounts for 0.1%-10% of the mass of the sulfide solid electrolyte membrane; and / or, the particle size of the sulfide electrolyte is 1 μm-200 μm; and / or, the thickness of the sulfide solid electrolyte membrane is 10 μm-100 μm.

11. The method according to claim 1 or 2, characterized in that, During the preparation of the sulfide solid electrolyte membrane, the materials can be mixed by at least one of a mechanical stirrer, a magnetic stirrer, a ball mill, and a thinky.

12. The method according to claim 1 or 2, characterized in that, When heating and mixing, the heating temperature is 50°C-80°C, and the heating time is 1 min-30 min; and / or, when drying, the drying temperature is 60°C-100°C, and the drying time is 1 h-20 h.

13. A sulfide solid electrolyte membrane, characterized in that, The sulfide electrolyte membrane is prepared by the method according to any one of claims 1 to 12.

14. A all-solid-state battery, characterized in that, Comprising: a positive electrode, a negative electrode, and the sulfide solid electrolyte membrane of claim 13.

Citation Information

Cited By

  • A modified sulfide solid electrolyte, a sulfide solid electrolyte membrane, and a preparation method and applications thereof

    CN122638596A